The Best of Both Worlds: The Role of Career Adaptability and Career Competencies in Students’ Well-Being and Performance - Akkermans, Jos; Paradniké, Kristina; Van der Heijden, Beatrice I. J. M.; De Vos, Ans (Frontiers in Psychology, 2018)
In addition to acquiring occupation-specific knowledge and skills, students need to develop a set of career self-management skills – or resources – that helps them to successfully maneuver the various career-related challenges they face and that stimulate their well-being, engagement, and performance in studying tasks. In the current study, we apply the Job Demands – Resources (JD-R) theory in an educational setting and suggest that career adaptability and career competencies are important career resources that predict both life satisfaction and academic performance via students’ satisfaction with the choice of their major and study engagement. Undergraduate students (N = 672) from nine different colleges and universities in Lithuania participated in the study. The results revealed that career adaptability and career competencies were positively linked to students’ life satisfaction, both directly and via study engagement. In addition, these career resources were positively, yet indirectly, related to academic performance via study engagement. Overall, the results suggest that career-related resources contribute to study engagement, life satisfaction, and academic performance. The results of our study further support JD-R theorizing and its applicability in student samples. Further theoretical and practical implications are discussed.